Evaluasi RPP Berdasarkan Prinsip Pembuatannya Dalam Permendikbud Nomor 22 Tahun 2016 Pada Guru Sejarah di SMAN 3 Padang Panjang - Khoirul Ihwan; Hera Hastuti (Jurnal Kronologi, 2020)
This research is motivated by various problems in the Learning Implementation Plan (RPP) made by the teacher of SMAN 3 Padang Panjang. The problems are (1) imperfect preparation of lesson plans by the history teacher of SMAN 3 Padang Panjang, (2) teachers only copy the existing lesson plans to copy lesson plans from other schools. This study aims to evaluate the quality of the lesson plans for the history teachers of SMAN 3 Padang Panjang whether they are in accordance with the principles of the preparation of lesson plans according to Permendikbud No.22 of 2016, then what are the obstacles faced by teachers in the manufacturing process. The method used in this study is an evaluative study, the source of the data in this study was obtained directly from informants in the field through interviews and document studies in the form of a history teacher lesson plan at SMAN 3 Padang Panjang. The findings of this study indicate that the teacher's lesson plan is in accordance with the Ministry of Education and Culture Regulation No.22 2016. However, the quality of the teacher's lesson plan is not yet ideal because there are still errors in distinguishing between the tools and media included in the lesson plan and the difficulty of teachers in matching the model used with KD and learning material to be taught.